The Complex Molecular Picture of Gut and Oral Microbiota–Brain-Depression System: What We Know and What We Need to Know - Scassellati, Catia; Marizzoni, Moira; Cattane, Nadia; Lopizzo, Nicola; Mombelli, Elisa; Riva, Marco Andrea; Cattaneo, Annamaria (Frontiers in Psychiatry, 2021)
Major Depressive Disorder (MDD) is a multifaceted mental disorder characterized by dysfunctions in neurochemical, neuroendocrine, immune and metabolic systems. The microbiota-gut-brain axis is a bidirectional network linking the central and enteric nervous system through the same endocrine, immune, neural, and metabolic routes that are dysregulated in MDD. Thus, gut-brain axis abnormalities in MDD patients may, at least partly account for the symptomatic features associated with MDD. Recent investigations have suggested that also the oral microbiome plays a key role in this complex molecular picture of relationships. As on the one hand there is a lot of what is known and on the other hand little of what we have yet to know, we structured this review into two specific sections: the first focusing on putting all pieces of this complex puzzle together, underlying that the endocrine, immune, oxidative stress, neural, microbial neurotrasmitters and metabolites molecular interactions and systems lay at the base of gut microbiota (GM)-brain-depression interphase. In the second section, we discussed the research on the potential role played by the gut phageome, bacteria-infecting viruses, that although they are the largest portion of the human gut virome, are the one of the least studied residents due to challenges associated with studying these difficult to culture entities. In addition, we focused the potential interconnection with oral microbiome that, along with GM, can influence the neuroinflammation-related processes and thus, to be potentially involved as well in the etiological processes underlying MDD. As conclusions and future directions, we discussed potentiality but also pitfalls, roadblocks and the gaps to be bridged in this exciting field of research. Developing a broader knowledge of the biology associated with MDD, with the inclusion of the microbiome, promotes increases in global health and brings clinical science closer to the vision of individualized medicine.